Konsekuensi dari Influencer Endorsement - Muhammad Rizky Ananda; Dhafa Zulfikar Alfarissy Mawardi; Fatik Rahayu (Journal on Education, 2023)
The purpose of this study is to obtain related empirical evidence: To analyze the positive influence of Influencer Endorsement and Brand Trust on Repurchase Intention. The sampling technique in this study used "purposive sampling" with the criteria of respondents being individuals who “Followed Otomotif Influencer on Social Media ". In this study, the primary data was obtained from a questionnaire made using the Google Form and distributed to 228 respondents. The results of this study indicate that there is a positive influence from Influencer Endorsement on Repurchase Intention and a positive influence on Brand Trust and Repurchase Intention.